The Basic Entity Model: A Fundamental Theoretical Model of Information and Information Processing - Liang, Thow Yick (Institutional Knowledge at Singapore Management University, 1994)
Management information systems (MIS) is a young and dynamic technological discipline that is greatly in need of a theoretical foundation in order to be recognised as an academic field. A key to this search is the construction of a paradigm which engulfs a set of objects that is genuinely indigenous to MIS. This study is a modest attempt to identify this set of objects and to construct a simple model based on them. A basic entity model is constructed to provide a better understanding for the fundamental theory of information. The model identifies the four basic entities which define the scope of information theory and establishes the three fundamental postulates which can serve as its foundation. The four basic entities are data, information, knowledge, and wisdom. The order of the entity as specified is important. Each entity is transformed to the next higher one during entity processing (information processing). The transformation taking place during entity processing reduces the entropy of the entity so that further analysis can be executed more systematically. This concept enforces the fact that all computerized information systems also have a similar basic role.